Carrot (Doucus Carota) Farming Analysis; Case Study in Pattapang Village, Tinggimoncong District, Gowa Regency - Nadratannaimi Nadratannaimi; Iis Ferawati Bakri; A. Yamna Yusria; Hermawan Saputra; A. Muhammad Amar Ma’ruf (Newinera Publisher, 2021)
The objectives of this study are to: (1) determine the production of carrot farming; (2) identify the net revenue of carrot farming; and (3) determine variations in the price of carrots in Pattapang Village, Tinggimoncong District, Gowa Regency. The investigation was carried out in Pattapang Village, Tinggimoncong District, Gowa Regency, South Sulawesi Province, and the place was chosen with care. The number of farmers that participated in this research was five individuals. The findings revealed that the average revenue from carrot growing. Farmers in Pattapang Village earn 26,364,000 IDR per hectare through carrot growing, with expenditures spent of 1,204,940 IDR per hectare, for a total revenue of 25,046,560 IDR per hectare